Reading the death of Mrs A: a serious case review. Issue 5 (12th October 2015) - Foley, Marian; Cummins, Ian
Abstract : Purpose: – The purpose of this paper is to report the main themes identified into the Serious Case Review (SCR) produced by Surrey Safeguarding Adults Board (SSAB) regarding the suicide of Mrs A in January 2013. Design/methodology/approach: – A case study approach is used to examine the SCR. The paper links the findings of the SCR with the broader literature, which has examined the experiences of witnesses and complainants in cases of sexual violence. Findings: – The report emphasises that support for witnesses in historic sexual assault cases has improved but there are still significant gaps in provision. In particular, the systems need to support witnesses for longer after giving evidence. Mental health services need to be more aware of the potential impact of Court cases on victims of sexual violence. The case also highlights the potentially devastating impact of the media reporting of evidence given by victims in rape cases. Practical implications: – The authors hope that a wider consideration of the circumstances of this case will lead to a greater focus on the needs of victims in cases of historic rape and other sexual assault cases. The SCR highlights that the provision of support for women giving evidence in sexual abuse cases is patchy. Such cases raise very serious ethical issues including the question of how to use the special measures that exist to support vulnerable or intimidated witnesses. Originality/value: – The paper brings together a number of themes in the wider literature and links them to current practice. It also uses a case study approach to exploring the implications for women, in cases of historical sexual abuse, of giving evidence in Court proceedings.